Traumatic Brain Injuries: A Cross-Sectional Study of Traumatic Brain Injuries at a Tertiary Care Trauma Center in the Punjab, Pakistan. (28th February 2023) - Rahman, Usama; Hamid, Moaz; Shan Dasti, Muhammad; Nouman, Tahir; Vedovelli, Luca; Javid, Azhar
Abstract: Introduction: Traumatic brain injuries (TBIs) are 1 of the most common reasons for young adult death and disability. This study sought to provide novel data for TBIs in Southern Punjab, as well as to identify any areas of service improvement to reduce the acute and long-term burden of this condition. Methods: A survey in English was created, which was then circulated to members of the emergency and neurosurgical department for a 3-wk period. Results: A total of 450 patients (379 male [84.2%] and 71 female [15.2%]) were included as TBI admissions or attendances with a mean age of 28.9 y. Of the total, 420 people (93.2%) had experienced a TBI following a road traffic incident (RTI), with 78.7% ( n = 354) of TBIs involving motorbike users who were not wearing helmets. A total of 226 (50.1%) patients arrived by car to the hospital, and 201 (44.7%) arrived by means of provincial government-funded emergency ambulance services. Conclusions: TBIs in Southern Punjab mostly affect younger males involved in RTIs while riding motorbikes. Recommendations to reduce the acute and long-term burden of TBIs in this region include formal training of all hospital and prehospital staff in the management of acute trauma cases according to international guidelines and operating provincial government emergency ambulance services in a wider geographic area.